Relevance of a preventive model of osteomyoarticular lesions in young adults - Ernesto Sánchez Hernández; Gertrudis de la Torre Vega; Lisbet Estrada Ladoy; Mislay Rodríguez García; Nadina Travieso Ramos (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: Osteomyoarticular lesions among young people that render services for the defense are related to risk factors. The use of preventive models bases its approach on the identification of risk and development of actions for its prevention. Consent methods are used for their validation and participative models, interpretative and constructivist valuations on their processes back the evaluation of its impact.  Objective: To evaluate the relevance of the preventive model for identifying the risk of osteomyoarticular lesions  in young adults of an armed institution.  Methods:  An investigation was carried out on January 2024, which included 16 experts and 125 young adults from Santiago de Cuba province. For the model validation the experts' criteria method was used and for the evaluation of  impact, the  Guba and Lincoln Fourth Generation Model. Results: With similar percentage values and  differences in the cut points, in both rounds, the consent got into groups in the categories of quite appropriate (25.0 %) and very appropriate (75.0 %). The result was interpreted as significant and the validation was concluded. The evaluation of impact in the preventive actions reached strong agreement (Me=8; IC 7-9) and appropriate degree of recommendation with value higher than 70.0 % of consent among  assessors.  Conclusions: The relevance of the model is demonstrated in the consent that reflects the capacity to guarantee precision when measuring the prospective results and the impact that projects an appropriate degree of recommendation on the proposed actions.